Mechanized scaling with ultrasonics: Perils and proactive measures - Rashmi Paramashivaiah; M. L. V. Prabhuji (Wolters Kluwer Medknow Publications, 2013)
Mechanized scaling for plaque removal is a routine procedure in the practice of periodontics. Though it appears innocuous by itself, there are retinues of hazards associated with it on various organ systems in the body. Some of these unwanted effects and measures to avoid or ameliorate the same are elaborated here. Exposure to ultrasonic scaling is inevitable before any other treatment procedure. Aerosol contamination, vibrational hazards, thermal effects on the dental pulp, altered vascular dynamics, disruption in electromagnetic device, diminished hearing and dental unit waterline contamination are some of the probable off-shoots a patient has to bear. Uses of barrier devices, proper attention to usage of equipment, protection for ear and water treatment are few of solutions for the same. Though documented evidence for the existence of all effects is lacking, it is never the less significant for the overall safety of the patient. A conscientious clinician should therefore inculcate the available steps to overcome the hazards of ultrasonic scaling.